The Impact of Word of Mouth on Motion Picture Industry - Hao, Jie (2008)
Purpose--Considering the lack of investigation on this topic, the aim of this research is to offer the insight of the impact of word of mouth on the motion picture industry. It seeks to analyze the nature of WOM in the motion picture industry and the relationship between the WOM and the box office sale. The antecedences of WOM in the motion picture industry are examined as well. Methodology--Online user reviews of 50 movies with regard to the WOM volume and valence from Yahoo!Movies are collected to test the relationship between the WOM and the box office revenue. Other variable, such as stars, genres, and critic opinion, come from various website to examine the antecedences of WOM. Findings--This study confirms that WOM plays the dual role of driver and outcome. The volume of WOM, rather than the valence of WOM provides the significant explanatory power for box office sales for the movie in general. However, the valence of WOM does have effect on the box office revenue and the volume of WOM for drama movies. Moreover, the WOM is very dynamic where the WOM volume and the valence change over time. The valence of WOM is mostly positive during the prerelease period due to the high expectation. The antecedents of WOM vary, in the different stages a particular movie situated. During the pre-released period, the genres, critics' opinion mostly determine the WOM volume. However, the critics have little influence on the WOM volume and valence after the movie is released. Surprisingly, the star power is not found to be influential on WOM. The WOM volume and box office revenue in the previous week have a great effect on the WOM volume after the movie is released. Implication-- WOM is very active during the pre-released period, and the WOM volume has a great effect on the box office revenue. Managers should create the buzz beyond the new movie itself. Moreover, the findings indicates that studio managers should try to create as much WOM communication as possible, observe and response to consumers' WOM actively due to the strong effect of WOM volume on the box office sales, especially during the opening weeks when most box office revenue is created. Furthermore, different strategies should be designed based on different genres. Although the WOM valence is not very important for adventure/action and animation, it has some effect on the drama movies. The findings also contribute to the existing literature on WOM. This approach changes the casual relationship between the WOM and the box office revenue, which demands researchers to pay attention to. Moreover, one of the most significant contributions this study makes is that it studies different genres separately, and reveal the interesting result from it. Limitations-- This study uses the online user review to generate the data; however, there is only one type of data source. The dynamics of WOM dissemination might be changed if gathering data from the online social communities. Moreover, the way this study construct the star power limits the results and findings. In addition, all movies were grouped roughly, and were categorized based on the researcher's subjective judgment. In the future, each genre can be studied separately in order to provide studio manager more specific suggestion.